Efektivitas Komunikasi Interpersonal Kepala Sekolah dalam Meningkatkan Kinerja Guru - Nurasiah Nurasiah; Zulkhairi Zulkhairi (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
This study aims to obtain information about the process and effectiveness of interpersonal communication principles in improving performance at Lhokseumawe 2 Public Middle School. The method used in this study is a qualitative method with a descriptive approach. The research data source consisted of principals, administration section, parts and infrastructure, and teachers. Data collection techniques through interviews, observation, and documentation. Data analysis uses data collection, data reduction, data presentation, and drawing conclusions or data verification. The results showed that the process of interpersonal communication in improving the performance of the teacher applied, there were two communication perspectives used namely psychological and mechanical. And use two types of verbal and nonverbal communication, both types of communication are used based on the needs that occur in the field. Regarding the effectiveness of interpersonal communication in increasing teacher performance, to obtain effective communication, there are several interpersonal communication indicators used, namely: openness, empathy, support, positive behavior, and similarities.